2016
DOI: 10.4274/tjh.2014.0385
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes of Mannose-Binding Lectin, H-Ficolin, and Procalcitonin in Patients with Febrile Neutropenia: A Prospective Observational Study

Abstract: Objective:The significance of mannose-binding lectin (MBL) and H-ficolin deficiency in febrile neutropenic (FN) patients and the correlation of these markers along with consecutive C-reactive protein (CRP) and procalcitonin (PCT) levels during the infectious process are investigated.Materials and Methods:Patients with any hematological malignancies who were defined to have “microbiologically confirmed infection”, “clinically documented infection”, or “fever of unknown origin” were included in this single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
2
4
1
Order By: Relevance
“…Furthermore, data from several other studies (concerning patients with other leukaemias, or haematological malignancies in general) led to similar conclusions [41][42][43][44][45][46] . In contrast to our results presented here and in afore-mentioned recent paper 37 , some earlier reports suggested that low MBL (or associated genotypes) enhanced the risk for infections in such cases 31,32,36,[47][48][49][50] . Furthermore, it was demonstrated that L-asparaginase (used in ALL treatment) induces a marked decrease in MBL concentration, which was suspected to contribute to increased risk of febrile neutropenia with infection 51 .…”
Section: Aml Aml-a Aml-b Aml-c Aml-dcontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, data from several other studies (concerning patients with other leukaemias, or haematological malignancies in general) led to similar conclusions [41][42][43][44][45][46] . In contrast to our results presented here and in afore-mentioned recent paper 37 , some earlier reports suggested that low MBL (or associated genotypes) enhanced the risk for infections in such cases 31,32,36,[47][48][49][50] . Furthermore, it was demonstrated that L-asparaginase (used in ALL treatment) induces a marked decrease in MBL concentration, which was suspected to contribute to increased risk of febrile neutropenia with infection 51 .…”
Section: Aml Aml-a Aml-b Aml-c Aml-dcontrasting
confidence: 99%
“…Several earlier reports 31,32 suggested a lack of association of ficolin-2 and/or ficolin-3 with incidence of infections or febrile neutropenia in patients with various haematological cancers. However, low ficolin-2 was suggested to predict higher risk of development of sinusoidal obstruction syndrome (SOS) after allogeneic haemopoietic cell transplantation 33,34 while low ficolin-3 was considered a risk factor for febrile neutropenia (also accompanied with bacteremia) in children, treated with anti-cancer chemotherapy 35 .…”
Section: Aml Aml-a Aml-b Aml-c Aml-dmentioning
confidence: 97%
“…Even though lactate was the most specific marker in our study, we believe that its low sensitivity limits its use in the diagnosis of FN. Procalcitonin levels of febrile neutropenic patients significantly increased and procalcitonin levels can be applied for the early diagnosis of infection in neutropenic patients (12). Our results we obtained in compliance with other studies.…”
Section: Discussionsupporting
confidence: 90%
“…The profile of changes of ficolin-3 levels in patients was generally similar to that demonstrated for ficolin-2. No impact of ficolin-3 on incidence of infections or febrile neutropenia in adult patients with hematological malignancies was previously reported by Ameye et al (49), Kilpatrick et al (50), and Islak Mutcali et al (54). Low ficolin-3 concentration was however suggested to be a risk factor for febrile neutropenia (especially with bacteremia) in pediatric cancer patients treated with chemotherapy (55).…”
Section: (B)mentioning
confidence: 85%